2006
DOI: 10.1038/sj.ijo.0803330
|View full text |Cite
|
Sign up to set email alerts
|

Childhood intelligence, educational attainment and adult body mass index: findings from a prospective cohort and within sibling-pairs analysis

Abstract: Background:The mechanisms underlying the observed association of childhood intelligence with body mass index (BMI) are unclear and few studies of this association have been prospective in design. Methods: Prospective study in a birth cohort of 5467 individuals who were born in Aberdeen, Scotland between 1950 and 1956 and who responded to a follow-up survey in 2001. Comparison of associations within sibling pairs of the same family to associations between different families in 643 sibling pairs (1286 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
46
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 23 publications
11
46
0
Order By: Relevance
“…In Britain, as in many other countries, social and behavioral pathways are intertwined because of the strong influence of social circumstances on behaviors. Not surprisingly, effects of adjustment for adult social circumstances were found to be substantial, as reported for associations of childhood cognition with all-cause mortality, 9 obesity, 5,6 and risk factors investigated here.…”
Section: Comparison With Other Studiesmentioning
confidence: 63%
See 1 more Smart Citation
“…In Britain, as in many other countries, social and behavioral pathways are intertwined because of the strong influence of social circumstances on behaviors. Not surprisingly, effects of adjustment for adult social circumstances were found to be substantial, as reported for associations of childhood cognition with all-cause mortality, 9 obesity, 5,6 and risk factors investigated here.…”
Section: Comparison With Other Studiesmentioning
confidence: 63%
“…3,4 Associations between higher childhood cognition and lower levels of adiposity have been observed, with some studies investigating mediation of factors such as adult education. [5][6][7][8] Explanations have been proposed for associations between childhood cognition and adult mortality or morbidity: first, there may be common causes of cognition and adult disease, including childhood socioeconomic position; second, childhood cognition predicts later educational and occupational attainment, which in turn influences exposure to hazardous environments that affect risk of adult disease; and third, childhood cognition affects the extent to which individuals acquire or act on knowledge about protective or health-damaging behaviors linked to disease. 9 Few studies have examined explanations in detail, largely because of limited data availability on relevant factors.…”
mentioning
confidence: 99%
“…Furthermore, measures of intelligence (IQ) correlate with important life outcomes pertaining to educational achievement, job performance, wealth, and health status (Deary et al 2007;Gottfredson 1997;Gottfredson and Deary 2004;Lawlor et al 2006). Importantly for modern theories of decision making, differences in IQ consistently predict parameters describing individuals' preferences with respect to risk and temporally delayed rewards (Burks et al 2009;Rustichini et al 2009;Shamosh et al 2008;Shamosh and Gray 2008), suggesting that these fundamental decision parameters may be critically influenced by common neurobiological mechanisms related to intelligence.…”
mentioning
confidence: 99%
“…A recent study (Ariansen I, In press) carried out in a population overlapping the present found that one third of educational differences in CVD risk factors could be explained by early life factors shared by siblings. Lawlor et al [26] reported an attenuation of the association between BMI and education in within siblingship analyses. Kamphuis et al [27] found that childhood circumstances more or less completely influenced cardiovascular mortality through known CVD risk factors.…”
Section: Explanations Of Resultsmentioning
confidence: 99%